Sociological and Socio-Psychological Dimensions of Well-Being and Happiness Rating Based on ISSP Data, 2018 - Todorova, Elka (Research Papers, 2019)
This article examines the main sociological and social psychological arguments when operationalizing empirically the concepts of "well-being" and "happiness". Using data for Bulgaria in ISSP 2018 we examine several hypotheses related to different sociological and social psychological effects taking place in the process of self-assessments, i.e. hedonic relativism and aspirational treadmill, the influence of education on the cognitive part of the subjective well-being and susceptibility to attitudinal changes in respondent’s traditional worldview.